Magilumiere Magical Girls Inc. 1 - Iwata, Sekka (Viz signature., 2024)
There's never a dull day at the office when you're a magical girl! Are you looking for something new? Something challenging? Something very highly paid? Exterminating monsters is an exciting, fast-paced field that will get you out from behind a desk and into the action. With over 500 magical girl companies now in operation, you're sure to find a position--and a uniform--that fits. Start your career as a magical girl today! Kana Sakuragi is an excellent candidate for the job. Any job! She's motivated and organized, and has a fantastic memory. So why has she interviewed at over 15 companies without receiving a single offer? She's trying to keep a positive attitude, but it seems like her bad luck is only getting worse when a monster crashes her latest interview. As havoc ensues, she finds herself helping the magical girl who comes to their rescue and ends up with more than just her life in return. Meet the newest magical girl at Magilumiere Magical Girls Inc.!